Effect of Liquid Nitrogen Cooling and Heating on Mechanical Properties and Acoustic Emission Characteristics of Coal - Yuhe Cai; Yi Xue; Faning Dang; Linchao Wang; Xue Li; Shanjie Su; Shengcheng Wang; Xinyu Liang; Shaowei Zhang (Geofluids)
The instability of rock fractures has been extensively studied in domestic and international research. This paper investigates two coal types from the Jiaozuo area, which were subjected to liquid nitrogen cyclic treatment using Brazil’s indirect tensile testing (BITT). The study analyzes the characteristics of acoustic emission (AE) and crack formation during the coal cracking process and evaluates the impact of freeze-thaw treatment with liquid nitrogen cycles on the mechanical properties of coals. The results demonstrate that liquid nitrogen has a significant impact on the formation and development of coal fractures under the Brazil splitting test conditions. As the number of cyclic treatments increases, the maximum load-bearing capacity of coal decreases, indicating a gradual reduction in the effective stress on coal samples. Furthermore, the acoustic emission activity intensity of coal mass during phased loading increases as the number of freeze-thaw cycles of liquid nitrogen increases. Finally, during phased loading of coal specimens, the primary factor is the germination, extension, and failure of tensile cracks, while the secondary factor is the development, extension, and failure of shear cracks. Overall, this study provides valuable insights into the behavior of coals under freeze-thaw cycles of liquid nitrogen treatment and highlights the importance of understanding the characteristics of coal fracture instability.